Riwayat Penyakit Kronis dengan Kejadian Jatuh pada Lansia - Chandra Kirana; Asri Handayani Solihin; Supriadi Supriadi (Jurnal Sehat Masada, 2024)
The history of chronic diseases that many elderly suffer from is hypertension, diabetes mellitus, heart and joints and the elderly have consequences for falling. History of chronic disease in Sumedang Regency was 33.1%, joint disease was 14.5%, stroke was 4.6% and heart was 6.7%, while 3 people fell. The type of research used is descriptive and correlative with a cross-sectional approach. The sample of this study was the elderly with a total of 57 people who were selected based on a purposive sampling technique using criteria. The research instrument used is a questionnaire. The analysis used is univariate and chi-square tests. The results showed that 66.7% of the elderly had a history of chronic joint disease and 73.7% of the elderly had experienced falls and a value of (p=0.000) was obtained. In conclusion, there is a relationship between a history of chronic disease and the incidence of falls in the elderly. Suggestions for the Public Health Centre to develop a fall prevention program by reducing chronic diseases in the elderly through Prolanis and Posbindu activities.